2019
DOI: 10.1017/s003329171900285x
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drugs v. barbiturates or benzodiazepines used as active placebos for schizophrenia: a systematic review and meta-analysis

Abstract: BackgroundComparisons of antipsychotics with placebo can be biased by unblinding due to side effects. Therefore, this meta-analysis compared the efficacy of antipsychotics for acute schizophrenia in trials using barbiturates or benzodiazepines as active placebos.MethodsRandomized controlled trials (RCTs) in acute schizophrenia with at least 3 weeks duration and comparing any antipsychotic with barbiturates or benzodiazepines were eligible. ClinicalTrials.gov, CENTRAL, EMBASE, MEDLINE, PsycINFO, PubMed, WHO-ICT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…We did not suggest that antipsychotics are merely active placebos, nor that they are identical in their effects to other sedatives. In line with Siafis et al (2019), we pointed out that some trials found that antipsychotics were superior to barbiturates for the treatment of schizophrenia, but that current evidence has not established that they are different from benzodiazepines in their effectiveness. What we also suggested was that there is no evidence that antipsychotics, or any other drug prescribed for a mental disorder, produce their therapeutic effects by reversing an underlying brain-based abnormality.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…We did not suggest that antipsychotics are merely active placebos, nor that they are identical in their effects to other sedatives. In line with Siafis et al (2019), we pointed out that some trials found that antipsychotics were superior to barbiturates for the treatment of schizophrenia, but that current evidence has not established that they are different from benzodiazepines in their effectiveness. What we also suggested was that there is no evidence that antipsychotics, or any other drug prescribed for a mental disorder, produce their therapeutic effects by reversing an underlying brain-based abnormality.…”
supporting
confidence: 61%
“…We agree that it is important to establish whether antipsychotics are superior to other sedative drugs for the treatment of acute psychotic symptoms, and hence appreciate the review by Siafis et al (2019). We would like to correct a misperception of our work, however (Moncrieff & Cohen, 2005).…”
mentioning
confidence: 86%
“…Nevertheless, the public debate about psychotropic agents is often ideological rather than evidence-based. Therefore, although Professor Moncrieff did not explicitly write that antipsychotics are just unspecific sedatives, such arguments are often used making our systematic review important (Siafis et al, 2019).…”
Section: Correspondencementioning
confidence: 99%
“…We believe that our review further elucidated this discussion. We found sufficient evidence that antipsychotic drugs were superior to phenobarbital for acute schizophrenia, yet evidence on the comparison with benzodiazepines was inconclusive because it was based on a single small trial (80 participants including the inert placebo arm) with large response rates in all arms (65% in inert placebo and benzodiazepines, 75% in chlorpromazine), small doses of chlorpromazine (about 150 mg/day), and the trial being sponsored by the company manufacturing the benzodiazepines (Merlis, Turner, & Krumholz, 1962; Siafis et al, 2019). We also want to add that in a small trial (not meeting the inclusion criteria of our review because it was conducted in stable patients) in 53 patients with schizophrenia, diazepam was comparable to fluphenazine and superior to placebo in preventing progression to a full relapse when used for early signs of exacerbation after the abrupt discontinuation of antipsychotics (Carpenter, Buchanan, Kirkpatrick, & Breier, 1999).…”
Section: Correspondencementioning
confidence: 99%
“…A meta-analysis of RCTs comparing antipsychotics with barbiturates or benzodiazepines in the acute treatment of schizophrenia demonstrated that antipsychotics were significantly more effective than barbiturates, but there were inadequate data on benzodiazepines to draw any firm conclusions. 5 The findings rebut the challenge that effectiveness is a result of sedation or unmasking, although it is notable that the studies included are somewhat dated; a large contemporary RCT comparing antipsychotics with benzodiazepines would be interesting.…”
mentioning
confidence: 99%